2008
DOI: 10.1007/s12325-008-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s gangrene: Is it scrotal gangrene?

Abstract: Fournier's gangrene is still an important disease with high mortality rates in spite of the developments in intensive care units and new-generation antibiotics. It seems that there are no major differences between male and female patients in the characteristics of the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…It has been shown that FG affects patients with obvious immune compromise such as diabetes, alcoholism, immunosuppression, neoplasic disease and obesity. In the series of çakmak et al, 44.6% of patients had diabetes [6], 20% in the review of Eke et al compiling 1726 cases [1], and in our previous published series with 35 patients, 23 had diabetes [7]. Regarding etiologies, the anorectal origin seemed to be the more frequent one: 37% in the series of Brunet et al [5], 42% in the work of EL Mejjed et al [8], 42% I the series of Yilmazlar et al compiling 120 patients from one center [9], 72% in our series.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been shown that FG affects patients with obvious immune compromise such as diabetes, alcoholism, immunosuppression, neoplasic disease and obesity. In the series of çakmak et al, 44.6% of patients had diabetes [6], 20% in the review of Eke et al compiling 1726 cases [1], and in our previous published series with 35 patients, 23 had diabetes [7]. Regarding etiologies, the anorectal origin seemed to be the more frequent one: 37% in the series of Brunet et al [5], 42% in the work of EL Mejjed et al [8], 42% I the series of Yilmazlar et al compiling 120 patients from one center [9], 72% in our series.…”
Section: Discussionmentioning
confidence: 92%
“…Colostomy is mandatory for some authors [5,13] and optional for others [2,6,13,14]. It avoids fecal contamination of the wound and facilitates local healing.…”
Section: Discussionmentioning
confidence: 99%
“…In the genito-urinary tract, the principal causes are infections and instrumentation. [8,9] Predisposing factors for Fournier's gangrene include any condition with decreased cellular immunity (diabetes mellitus, alcoholism, malignancy, radiotherapy, chemotherapy, AIDS, steroid use, and malnutrition), local trauma, chronic renal failure, periurethral urine leak, perineal surgery, paraphimosis, and peripheral artery disease. [1,3,4,6,7,9,10] Obesity is also reported as a risk factor.…”
Section: Epidemiologymentioning
confidence: 99%
“…However, the disease was named after Jean-Alfred Fournier, a Parisian venereologist, on the basis of a transcript from an 1883 clinical lecture in which Fournier presented a case of perineal gangrene in an otherwise healthy young man, adding this to a compiled series of 4 additional cases 1 .It is generally accepted as synergistic necrotizing fasciitis of perineal, genital, or perianal regions 2 .It has been reported more in males than females 2 . It also occurs in neonates as seen in this case.…”
Section: Introductionmentioning
confidence: 99%
“…It also occurs in neonates as seen in this case. It was formally thought to be idiopathic 3 , however, studies and reports have proven its pathogenesis to colorectal diseases 4 , urogenital diseases 4 and Injury from urethal catherization 1 .In rare cases , vasectomy and circumcision and those with Diabetes mellitus 2,5 have been implicated among the etiologies . Furthermore, Fournier's gangrene could be the presenting sign of an undiagnosed human immunodeficiency virus infection 6 .…”
Section: Introductionmentioning
confidence: 99%